A global investment opportunity in non-listed infrastructure for institutional investors. Issue 3 (14th May 2020) - Marzuki, Muhammad Jufri; Newell, Graeme
Abstract : Purpose: Infrastructure investment is one of the few high-calibre real alternative assets with a strong prominence in the portfolios of institutional investors, especially those with a liability-driven investment strategy. This has seen increased institutional investor interest in infrastructure for reasons such as diversification benefits and inflation hedging abilities, resulting in the substantial growth in non-listed and listed investment products offering access to the infrastructure asset class, and complementing the existing route via direct investment. This paper aims to assess the investment attributes of non-listed infrastructure over Q3:2008–Q2:2019, compared with other global listed assets of infrastructure, property, stocks and bonds. Design/methodology/approach: Quarterly total returns were derived from the valuation-based MSCI global non-listed quarterly infrastructure asset index over Q2:2008–Q:2019, which were then filtered to decrease the valuation smoothing effects. A similar set of returns data was also collected for the other global asset classes. The average annual return, annual risk, risk-adjusted performance and portfolio diversification benefits for non-listed infrastructure and other asset investment classes were then computed and compared. Lastly, a constrained optimal asset allocation analysis was performed to validate the performance enhancement role of global non-listed infrastructure in a mixed-asset investment framework. Findings: Global non-listed infrastructure delivered the strongest average annual total return performance, outperforming the other asset classes and provided investors with total returns that linked strongly with inflation. Global non-listed infrastructure also provided investors with one of the least volatile investment returns because of its ability to ensure predictable total returns delivery. This means that on the Sharpe ratio risk-adjusted return basis, non-listed infrastructure was also the strongest performing asset. This performance was also delivered with significant portfolio diversification benefits with all assets, resulting in non-listed infrastructure contributing to the mixed-asset portfolios across the entire portfolio risk spectrum. Practical implications: Aside from better risk-return trade-offs, institutional investors are getting more secular with their portfolios for alternative assets that are able to provide other investment benefits such as predictable long-term performance and inflation-linked returns. A further improvement in performance and diversification benefits could be achieved by enriching existing investment portfolios with real alternative assets, one of which is the infrastructure asset class. For institutional investors, having exposure to and being part of the development, delivery and management of infrastructure assets are important, as they are one of the few real assets having considerable significance in the context of society, economy and investment needs. Originality/value: This is the first research paper that empirically investigates the investment attributes of the non-listed infrastructure at a global level. This research enables empirically validated, more informed and practical decision-making by institutional investors in the infrastructure asset class, especially via the non-listed pathway. The ultimate aim of this paper is to empirically validate the strategic role of non-listed infrastructure as an important alternative asset in the institutional real asset investment space, as well as in the overall portfolio context.